A novel degradable PEG superparamagnetic iron oxide capsule coupled with a polyphenolic nano-enzymatic conjugate (PSPM-NE), to treat ROS-driven cardiovascular-diseases, tested in atherosclerosis as a model disease, and hypothesizing autoimmunity as an atheroma's trigger - Pereira, Glaucia C. (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular diseases account for a significant portion of the worldwide mortality rate. This aroused interest among the specialised scientific community, seeking for solutions based on non-clinical and clinical investigations, to shed light onto the physio-pathology of cardiovascular impairment. It is proven challenging managing chronic cardiovascular illnesses like atherosclerosis, arrhythmias, and diverse cardiomyopathies. In certain cases, there is no approved treatment. In other cases, the need for combining therapeutic components, when dealing with co-morbidities, may increase the risk of toxicity-driven cardiovascular impairment. In this case, because the risk of cardiac events correlates with the QT prolongation rates, the QT or QTc interval prolongation has become an important biomarker to access drug-related cardio-toxicity. Several approaches have been found in the current literature, aiming at improving physiological acceptance, i.e., to reduce toxicity. Nanotechnology has increasingly appeared as a promising ally to modulate active substances, preserving cardiovascular function and optimising drug effectiveness, i.e., acting as a cardio-protective mechanism, leveraging the effects of drug-driven cardio-toxicity. In this manuscript, the author combines plant active compounds and nanotechnological strategies, e.g., nano-encapsulation, nano-enzymes, magnetically driven nano-delivery systems, applied in regenerative medicine, and assesses their effects on the cardiovascular system, e.g., as cardio-protective factors, reducing cardio-toxicity. The aim is to propose a new strategy to tackle atherosclerosis initiation and progression, in a drug design that targets ROS-removal and reduces inflammation, using auto-immunity biomarkers to select key atheroma-related signalling cascades. To analyse physiological phenomena related to atherosclerosis initiation and progression, the author proposes both experimental observations and a new haemorheological computational model of arterial constriction. The results of such analysis are used as motivators in the design of the here presented strategy to tackle atheroma. This novel design is based on degradable polyethylene glycol (PEG) superparamagnetic iron oxide capsule coupled with a polyphenolic nano-enzymatic conjugate (PSPM-NE).